Analisis Kesulitan Belajar Karena Gangguan Perkembangan Pada Anak Berkebutuhan Khusus di Sekolah Luar Biasa Tunas Kasih Surabaya - Saputra, Dhani Cahya; putri, Amalia Wulan Mahardika; Ahsyabila, Chantika Putri; Anggraeni, Fitriya Helen; Arum, Shaka Sekar; Amalia, Kaniati (CV Putra Publisher, 2025)
Children with special needs are children with different abilities from children in general who have their own way of dealing with learning. With the limitations they experience, children with special needs will face difficulties in learning. Learning difficulties experienced by children with special needs are usually due to developmental disorders of the child. This research was conducted with the aim of providing information to readers about the learning difficulties of children with special needs due to developmental disorders and the learning strategies applied to overcome the learning difficulties of children with special needs at SLB Tunas Kasih Surabaya. The data collection technique used in this research is qualitative research with interview, observation, and documentation methods where data is obtained directly from the source or first party by interviewing teachers and children with special needs directly. With this qualitative research technique, we can analyze data by presenting data and drawing conclusions. The result of this research is that in SLB Tunas Kasih has four categories of developmental disorders that cause learning difficulties from children with special needs, namely Tunagrahita, Deaf, Autistic, and Down Syndrome. It is hoped that this research can provide new knowledge and strategies for dealing with learning difficulties experienced by children with special needs so that it can be applied at SLB Tunas Kasih and other inclusive schools.